2018
DOI: 10.14746/ssllt.2018.8.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an online questionnaire of vocabulary learning strategies for ESL learners

Abstract: This article reports on the updating and validation of a questionnaire for vocabulary learning strategies. An English as a second language (ESL) version of the Vocabulary Learning Questionnaire (VLQ), first published in Gu and Johnson (1996), was created based on its latest version. Two response formats were piloted, that is, a paper version with a 7-point Likert scale and an online version with a 100-point slider bar. A series of validation procedures resulted in a 62-item instrument which was then administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 21 publications
0
72
0
3
Order By: Relevance
“…Vocabulary learning strategies pertain to actions that a learner takes to facilitate the completion of learning vocabularies (Gu, 2018). Empirical studies showed that effective VLS would enhance L2 language proficiency (Ajayi, 2015;Zhang and Lu, 2015;Susanto and binti Ab Halim, 2017), such as enlarging vocabulary size (e.g., Hamzah et al, 2009), and further determined second language context comprehension (Vedder and Benigno, 2016;Caro and Mendinueta, 2017).…”
Section: Literature Review the Classification Of Vocabulary Learning mentioning
confidence: 99%
See 1 more Smart Citation
“…Vocabulary learning strategies pertain to actions that a learner takes to facilitate the completion of learning vocabularies (Gu, 2018). Empirical studies showed that effective VLS would enhance L2 language proficiency (Ajayi, 2015;Zhang and Lu, 2015;Susanto and binti Ab Halim, 2017), such as enlarging vocabulary size (e.g., Hamzah et al, 2009), and further determined second language context comprehension (Vedder and Benigno, 2016;Caro and Mendinueta, 2017).…”
Section: Literature Review the Classification Of Vocabulary Learning mentioning
confidence: 99%
“…For instance, when they encountered new words while reading an article written in the target language, students would adopt a series of strategies such as looking up new words in dictionaries, consulting their teachers, and guessing the meanings of new words (e.g., Currie and Cain, 2015;Koyama, 2015;Graves et al, 2018). Gu (2018) used think-aloud protocols and interviews in her study of Chinese university learners of EFL and found that the students adopted meta-cognitive strategies, such as meta-jargon explanation, to figure out the meanings of new words when reading authentic texts.…”
Section: Past Studies On Vls Developmentmentioning
confidence: 99%
“…These properties replicated my intention to approach Libyan students and teachers widely in Libya within the timeframe available for the research programme, offering three data types: factual, behavioural, and attitudinal (Dörnyei & Taguchi, 2010). Questionnaires are suitable "for research with pedagogical purposes" that enables the "catching" of learning strategies (Gu, 2018) and provide a basic tool for investigating the perceptions of CSs or reporting the benefits or preferences regarding CSs usage in experimental studies (Wei, 2011). Oxford's (1990) Strategy Inventory for Language Learning (SILL) is possibly the most widely-recognised tool in the literature, which also assesses CSs (Nakatani, 2006).…”
Section: Rationale For the Questionnairesmentioning
confidence: 99%
“…Sections 2 and 3 investigate four different aspects of the two types of CSs, adopted from the taxonomy of . Questionnaires investigating language learning strategies usually present arrays of illustrative statements of the strategic behaviour, that the students are asked to rate to show how frequently they implement the strategy, and the learner's use of a stage is decided when a certain level of cumulative deployment of strategic learning behaviour is attained (Gu, 2018). The perceived use of the strategies in the Libyan classroom was alternatively assessed by asking the students to respond to "yes/no" questions for each strategy.…”
Section: An Overview Of the Final Questionnaire Designmentioning
confidence: 99%
See 1 more Smart Citation